2017
DOI: 10.5301/uj.5000250
|View full text |Cite
|
Sign up to set email alerts
|

Medical Treatment of Erectile Dysfunction: Too Many Medical Prescriptions?

Abstract: Erectile dysfunction (ED) is a worldwide commonly reported condition; epidemiological data showed a prevalence ranging from 2.3 to 53.4% within different population subsets. In this context, the advent of phosphodiesterase type 5 inhibitors (PDE5is) in the second mid of 1990s has deeply changed the treatment scenario of this bothersome condition. Being user-friendly compounds with an excellent overall safety profile, PDE5is emerged as the first-line treatment for ED, thus overcoming topical alprostadil and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
(187 reference statements)
0
3
0
Order By: Relevance
“…First and foremost, the largest health threats come from the use of wrong dosages of the intended drug − either too low to be effective, or at excessively high and possibly toxic levels, with large variations in drug contents. 6,59,67,125,129 The risk of overdosage of the medication is also possible for products with low content of the API, as consumers might be taking more than one tablet to achieve the desired effect. 6,18 However, in order to generate revenue and refrain the buyer to search for more efficacious products, counterfeiters are generally likely to use include the main API or similar active ingredients, or, as reported below, to add other APIs aiming to increase the efficacy.…”
Section: Regional Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…First and foremost, the largest health threats come from the use of wrong dosages of the intended drug − either too low to be effective, or at excessively high and possibly toxic levels, with large variations in drug contents. 6,59,67,125,129 The risk of overdosage of the medication is also possible for products with low content of the API, as consumers might be taking more than one tablet to achieve the desired effect. 6,18 However, in order to generate revenue and refrain the buyer to search for more efficacious products, counterfeiters are generally likely to use include the main API or similar active ingredients, or, as reported below, to add other APIs aiming to increase the efficacy.…”
Section: Regional Differencesmentioning
confidence: 99%
“…7 Counterfeit products are often produced in poor quality laboratories, resulting in the presence of residual solvents and contaminants in the finished product. 6,45,62,125,128,129 An analysis of counterfeited or illegal PDE5i collected between 2005 and 2011 in Italy reported that excipients were different than expected from a genuine product in 80% of analyzed samples, with presence of potentially toxic compounds in 17% of tablets. 19 These substances include ethanol, acetone, tetrachloromethane and dicloromethane 63 as well as paints and printer inks, 8 potentially harmful to the consumers as well as to the environment.…”
Section: Regional Differencesmentioning
confidence: 99%
See 1 more Smart Citation